Moving the world into a safe space–the GAPFRAME methodology. Issue 3 (November 2018) - Muff, Katrin; Kapalka, Agnieszka; Dyllick, Thomas
Abstract: In September 2015 the United Nations General Assembly unanimously adopted the 2030 Agenda for Sustainable Development with its 17 Sustainable Development Goals (SDGs), one of the most ambitious and important global agreements in recent history. To advance implementation of the SDGs, a new framework − the GAPFRAME − has been developed and published recently in this journal (Muff, Kapalka, Dyllick, 2017). The GAPFRAME highlights the gap between the current state of the world and a desired future state, defined as a "safe space", and identifies priority issues that need to be addressed on a national, regional, and global level. The www.gapframe.org website provides free access to the data collected for 196 countries and 22 regions across the world. This website was launched with the intention to provide decision-makers and stakeholders with aggregated information on the priority issues to be urgently addressed. The GAPFRAME focuses attention on addressing identified priority issues, holding each country or region accountable for the successful implementation of the global sustainability targets within their area of responsibility. It can be used as a planning tool, in particular for business, to identify long-term business opportunities. It can be also used as an educational tool to sensitize students to relevant sustainability problems and to evaluate and compare different sets of priorities. In this article, we explain in detail the GAPFRAME methodology, covering the different steps in the design of the framework, in scaling, normalization, weighting, and aggregating the information collected for the GAPFRAME Index V1 version. It will be best understood if the GAPFRAME concept is already known, but it can be read as well as a stand-alone article, primarily with a methodological focus. Highlights: The GAPFRAME is a tool to implement and monitor the SDG Agenda 2030. Indicators measure the gap of the current versus the ideal state in 24 issue areas. The GAPFRAME enriches the SDGs for a country-by-country equalized comparison. The GAPFRAME focuses stakeholders to priority issues at a national level. It is a tool for educators to sensitize students to understanding sustainability issues.